PENGARUH PENGGUNAAN MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP HASIL BELAJAR MATA PELAJARAN MATEMATIKA DI SDN 58 PALEMBANG - Rachel Sastriani; M. Taheri Akbar; Bambang Hermansah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine in depth the effect of using the Think Pair Share (TPS) learning model on the mathematics learning outcomes of fourth grade students at SDN 58 Palembang. The background of this study is the low student learning outcomes influenced by the lack of variation in learning methods applied by teachers in the classroom. This has an impact on the low participation of students in the learning process and their involvement in understanding the subject matter. This study uses a quantitative approach with a quasi-experimental design, specifically the Posttest-Only Control Group Design. The research sample consisted of two classes, namely the control class that received conventional learning treatment and the experimental class that used the TPS learning model. The research instrument was a multiple-choice objective test to measure student learning outcomes after the treatment was given. The results of data analysis showed that the average posttest score of students in the experimental class was 87.15 while the control class obtained an average score of 77.5. The t-test showed a significance value of 0.000 <0.05, which means there is a significant difference between the two groups. Therefore, it can be concluded that the use of the Think Pair Share learning model makes a significant contribution to improving students' mathematics learning outcomes. This model has also been proven to increase students' active participation, critical thinking skills, and self-confidence in expressing opinions during learning. This study recommends the use of TPS as an alternative active learning strategy in elementary schools.